Pengaruh Islamic Corporate Governance, Profitabilitas dan Size Terhadap Islamic Corporate Social Responsibility Pada Bank Umum Syariah di Indonesia - Riza Nur Rosita; Sri Lestari Kurniawati (JES (Jurnal Ekonomi Syariah), 2022)
This study aims to determine whether the islamic corporate governance, profitability and size of the company size influences the islamic corporate social responsibility in Islamic Commercial Bank in Indonesia. The sample in this study were 12 Islamic Commercial Bank in Indonesia for period 2016-2020. Data and methods of data collection in this study are secondary data obtained from annual reports on the website of Islamic Commercial Banks. The data analysis technique in this study use descriptive analysis, while for the statistical analysis the SPSS 16.0 test tool is used. The result of this study indicates that a)Islamic corporate governance, profitability and size simultaneously have a significant effect on Islamic corporate social responsibility,b) partially Islamic corporate governance has a significant positive effect on Islamic corporate social responsibility, c)partially profitability has a significant negative effect on Islamic corporate social responsibility and d)partially company size has insignificant effect on Islamic corporate social responsibility.